Response of broccoli to USG and prilled urea in shallow red-brown terrace soil under Madhupur tract (Bangladesh Journal of Agricultural Research, 2018)
A field experiment was conducted at Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur during the period from 2012-13 to verify the effectiveness of urea super granule (USG) and prilled urea (PU) on the yield and quality of broccoli, to assess the comparative performance of USG and PU on nutrient uptake and nitrogen use efficiency and to evaluate the effect of USG and PU on post-harvest nutrient status in Shallow Red-Brown Terrace Soil of Madhupur Tract (AEZ-28). The experiment was designed in a randomized complete block with three replications having 5 treatments as T1: Control, T2: USG-N140, T3: USG-N160, T4: USG-N180 and T5: PU-N180. Result showed that USG performed better than PU. The comparative performance of USG in relation to yield, head quality (ascorbic acid, β-carotene and chlorophyll content), SPAD value, nutrient (NPKS) uptake and N use efficiency was found higher as compared to PU. USG treated broccoli plants gave significantly higher yield where the highest yield (13.49 ton ha-1) was recorded with USG-N160 kg ha-1. Moreover, USG showed higher β-carotene and chlorophyll content over PU and those were increased with increasing levels of N. However, ascorbic acid content was slightly decreased with increasing rate of N fertilizer. Nitrogen, phosphorus and potassium uptake increased with increasing N rate upto USGN180 but sulphur uptake was increased upto USG-N160. Nitrogen use efficiency was higher in USG treated plots than that of PU having the highest value of 111.71% with USG-N160 kg ha-1. Post-harvest soil nutrient status was not significantly influenced by the treatments although it was slightly higher in USG as compared to PU. Considering all, USG @ 160 kg N ha-1 (USG-N160) with other recommended fertilizers (@ 53 kg P, 83 kg K, 20 kg S, 2.0 kg Zn, 1 kg B and 0.8 kg Mo ha-1) could be the best USG based fertilizer dose for quality broccoli production in Shallow Red-Brown Terrace Soil of Madhupur Tract.Bangladesh J. Agril. Res. 43(4): 557-574, December 2018